Cyberchondria and perceived stress: the mediating role of cognitive flexibility - Akat, Muhammed; Okur, Sinan; Akbulut, Omer Faruk; Hamarta, Erdal; Satici, Seydi Ahmet (SPRINGER, 2026)
This cross-sectional study aimed to examine the mediating role of cognitive flexibility in the relationship between cyberchondria and perceived stress, as well as to determine whether cyberchondria significantly differs by gender. The sample of the study consisted of 1328 adult participants (898 female, 67.6%). The participants, aged between 18 and 66, had a mean age of 28.204 years (SD = 8.555). In line with the objectives of the study, independent samples t-test and conditional process analysis were conducted. Subsequently, the significance of the mediating role was examined using the bootstrapping method. The correlation analysis indicated that all variables were interrelated. The study results revealed that cyberchondria scores were significantly higher among females (Cohen's d = 0.166) and that cognitive flexibility played a partial mediating role (indirect effect = 0.023, 95% CI [0.005-0.041]) in the relationship between cyberchondria and perceived stress. The findings were discussed in light of the literature, and suggestions for both researchers and mental health practitioners were provided for future directions.
Keywords: Cyberchondria; Cognitive flexibility; Perceived stress; HEALTH ANXIETY; DEPRESSION; RELIABILITY; GENDER; BIAS; Psychology